First description of male worms of Enterobius (Colobenterobius) serratus (Nematoda: Oxyuridae), the pinworm parasite of proboscis monkeys - Hasegawa, Hideo; Frias, Liesbeth; Peter, Surdensteeve; Hasan, Noor Haliza; Stark, Danica J.; Lynn, Milena Salgado; Sipangkui, Symphorosa; Goossens, Benoit; Matsuura, Keiko; Okamoto, Munehiro; Macintosh, Andrew J. J. (Zootaxa, 2020)
Males of Enterobius (Colobenterobius) serratus Hasegawa et al., 2003 (Nematoda: Oxyuridae) are described for the first time based on six individuals collected from the feces of proboscis monkeys, Nasalis larvatus, in the Lower Kinabatangan Wildlife Sanctuary, Sabah, Malaysian Borneo. The males show identical cephalic morphology to females, being readily distinguishable from their congeners by the serrated inner margins of the lips. The bicolored esophageal corpus, long thin spicule and developed spicular pouch with paired muscular bands are also remarkable characteristics, presumably shared by other Asian members of the subgenus.